Improving high school studentsâ€™ conceptual understanding of electricity and magnetism using scaffold analogy instructions - Mengistu, Aysheshim; Assefa, Shimels; Gebeyehu, Desta (Momentum: Physics Education Journal, 2022)
Simulated analogical teaching model has a novel contribution in enhancing studentsâ€™ learning. This study aims to analyze effect of simulated analogies scaffold by group discussion model in improving studentsÃ¢â‚¬â„¢ conceptual understanding of some selected contents of electricity and magnetism at high school level. The study involved 75 grade 10th students from two different high schools, namely Dagmawi Twodros and Fert high schools found in Debre Tabor Town, South Gondar, Amhara region, Ethiopia. A quasi-experimental method with pretest posttest design was used in the study. An adapted standardized test of electricity and magnetism conceptual understanding test (EMCUT) was used to collect data. The reliability of EMCUT was checked using KR-20 and found to be at about .81. After checking all necessary assumptions, an independent sample t-test was used to analyze the mean difference on students EMCUT scores between groups.Â  From the result analysis, we found that experimental group who used simulated analogies scaffold by group discussion method in learning of electricity and magnetism showed a higher mean score of EMCUT than the control group. Thus, it can be concluded that the use of simulated analogies scaffold by group discussion model improved high school studentsâ€™ conceptual understanding of electricity and magnetism.